2003
DOI: 10.1034/j.1600-0420.2003.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thick Tenon's capsule on primary trabeculectomy with mitomycin‐C

Abstract: The use of mitomycin-C is associated with high success rates and good IOP control even in the presence of thick Tenon's capsule. However, thick Tenon's capsule does not seem to eliminate the development of complications in eyes undergoing primary trabeculectomy with mitomycin-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…Mitomycin C is an antineoplastic-antibiotic agent produced by Streptomyces caespitosus that inhibits the synthesis of DNA, proteins and cellular RNA and is a potent inhibitor of fibroblasts proliferation. Drug use has improved not only recurrence rate after pterygium surgery but also the surgical results in other ocular disease, such as glaucoma, or corneal and conjunctival intraepithelial neoplasia 7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Mitomycin C is an antineoplastic-antibiotic agent produced by Streptomyces caespitosus that inhibits the synthesis of DNA, proteins and cellular RNA and is a potent inhibitor of fibroblasts proliferation. Drug use has improved not only recurrence rate after pterygium surgery but also the surgical results in other ocular disease, such as glaucoma, or corneal and conjunctival intraepithelial neoplasia 7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Histological studies have shown that proliferation of subconjunctival fibroplasts, which is believed to play an important role in bleb failure, occurs during the third to fifth postoperative day (Jampel et al 1988;Pescosolido et al 2002). Adjunctive antimetabolites, such as 5-fluorouracil (5-FU) and mitomycin-C, are commonly used to enhance the success of trabeculectomy (Azuara-Blanco et al 1997;Bindlish et al 2002;Akarsu et al 2003;Beckers et al 2003;Fraser 2004;Cillino et al 2008). However, the use of antimetabolites increases the risks of hypotony, bleb leakage and infection (Jampel et al 1992;Bell et al 1997;Nuijts et al 1997;Singh et al 1997;Spaeth & Mutlukan 2001;Lama & Fechtner 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Pathology studies have shown that, following trabeculectomy, migration, proliferation, and differentiation of the fibroblasts at the subconjunctival level, which are responsible for the fibrotic process and eventually the bleb failure, occur as early as the third to fifth postoperative day [ 8 , 9 ]. Adjunctive antimetabolites, such as 5-fluorouracil (5-FU) and mitomycin C (MMC), both intra- and postoperatively, are commonly used to enhance the long-term success of trabeculectomy [ 10 14 ]. However, due to their nonselective cytotoxicity, which could lead to conjunctival barrier breakdown, their use is not free of increased risk of complications, some of them devastating, such as ischemic and leaking bleb which could predispose to serious infections and even endophthalmitis [ 15 19 ].…”
Section: Introductionmentioning
confidence: 99%